The weight of dreams - Bhagwat, Jeevan (In Publications, 2012)
"The Weight of Dreams is a full length poetry manuscript that deals primarily with the theme of dreams and how they inform us from a conscious and unconscious perspective. It is intended for readers who are intrigued by how dreams play an important role in shaping our understanding of not only ourselves, but of our reality. The first part of the book is a long sequence poem entitled "The Weight of Dreams" which examines the romantic aspect of love and focuses on emotions resulting from loss and longing. The second part of the book consists of individual poems that deal with dreams and other issues."